Pengaruh Store Atmosphere, Food Quality, dan Service Quality Terhadap Keputusan Pembelian pada Kedai Bakso Sor Talok (Survei pada Pelanggan Bakso Sor Talok di Kabupaten Karanganyar) - Muhammad Rizki; Sumaryanto (Indo Publishing, 2025)
This study aims to analyze the influence of store atmosphere, food quality, and service quality on purchasing decisions of Bakso Sor Talok customers in Karanganyar Regency. This type of research is quantitative research with primary data sources. The population in this study were Bakso Sor Talok customers in Karanganyar Regency, with an unknown number. Sampling used non-probability sampling with purposive sampling technique, as many as 100 samples. Data collection techniques used questionnaires, observations and literature studies. The research instrument test used validity and reliability tests. The classical assumption test used multicollinearity, heteroscedasticity, autocorrelation and normality tests. The data analysis techniques used are multiple linear regression analysis, t-test, F- test, determination coefficient test (R2). The results of the validity and reliability tests show that all variables, namely store atmosphere, food quality, service quality and purchasing decisions are declared valid and reliable. The results of the classical assumption test show that all variables have passed the multicollinearity, heteroscedasticity, autocorrelation and normality tests. The results of the regression test show Y = 1.862 + 0.264 X1 + 0.160 X2 + 0.404 X3 + e. The results of the t-test show that store atmosphere (X1), food quality (X2), service quality (X3) have a positive and significant effect on purchasing decisions at the Bakso Sor Talok shop in Karanganyar Regency. The results of the F test obtained the results that the regression model used in this study was appropriate. The results of the R2 test showed that the contribution of the influence of the independent variables to the dependent variable was 64.8%. The rest (100% - 64.8%) = 35.2% is explained by other variables outside the model such as price, taste and location.